Can a trainee perform endovascular aortic repair as effectively and safely as an experienced specialist?. (9th November 2020) - Kosiorowska, Kinga; Berezowski, Mikołaj; Beyersdorf, Friedhelm; Jasinski, Marek; Kreibich, Maximilian; Kondov, Stoyan; Czerny, Martin; Rylski, Bartosz
Abstract: OBJECTIVES: Endovascular aortic repair (EVAR) is a technically demanding procedure usually carried out by highly experienced surgeons. However, in this era of modern endovascular surgery with growing numbers of patients qualifying for the procedure, the need to enhance surgical training has emerged. Our aim was to compare the technical results of EVAR in patients operated on by trainees to that of those operated on by an endovascular expert. METHODS: Between 2016 and 2018, a total of 119 patients diagnosed with an abdominal aorta disease requiring EVAR were admitted to our clinic. Overall, we included 96 patients who underwent preoperative and postoperative computed tomography angiography and EVAR performed either by an endovascular expert ( N  = 51) or a trainee ( N  = 45). RESULTS: We detected no difference in the baseline characteristics, indication for EVAR and preoperative anatomy between patients operated on by trainees and our endovascular expert. We noted the same incidence of endoleak type Ia occurrence ( n  = 2 vs n  = 2, P  = 1.00), reintervention rate ( n  = 0 vs n  = 0, P  = 1.00) and in-hospital mortality ( n  = 0 vs n  = 1, P  = 1.00) for operations done by trainees and the expert, respectively. There was no difference in X-ray doses or time between the 2 groups. Despite longer median operation times [112 (first quartile: 84; third quartile: 129) vs 89 (75–104) min; P  = 0.03] and in-hospital stays [10 (8–13) vs 8 (7–10) days, P  = 0.007] of the patients operated on by trainees, the overall clinical success of EVAR was satisfactory in both groups. CONCLUSIONS: An EVAR planned and performed by a trainee need not raise the cumulative risk of the procedure. Trainees who have undergone both mind and hand skills training can therefore carry out EVAR under the supervision of an experienced specialist as effectively and safely as experts do. Abstract : Thanks to its less invasive approach and low operative risk, endovascular aortic repair (EVAR) has earned broad acceptance as the preferred treatment for a broad range of pathological processes in the abdominal aorta, particularly abdominal aorto-iliac artery aneurysms [1–3].